Estilo de vida e saúde de um grupo de idosos de Franca, SP - Monteiro, Betânia de Andrade; Silva, Magali Conceição Monteiro da [UNESP] (My University, 2013)
The increase of elderly population in Brazil and all around the world shows the need of reviewing the health cares in order to get a better quality of life. Objective: To evaluate lifestyle and health care of elderly participants of UNATI, Franca, SP. Methods: Sixty elderlies answered a questions about socio-economic issues, health care, food consumption habits and lifestyle, after, they were submitted to anthropometric and laboratory tests. Results: There was a prevalence of women (85%), aged between 60-69 years old (60%), up to high school (60%), retired (65%), income up to 5 minimum wage (73.4%). Most seniors assessed medical care (65%) were in use of long-term medicines (78.3%), they reported to control blood pressure (80%) and to not smoke (100%). About 71.7% people believed to have a healthy diet, 97% took meals at home, 85% chose and prepared their own food, 65% had 5-6 meals/day, 63% drank 1L of water/day, 90% had bowel function and 43.3% practices a regular physical activity. Only 13.3% have done hormone replacement therapy, 18.3% take dietary supplements and 21.7% drink alcoholic drinks. The participants presented a BMI of 27.49 ± 4.5kg/m², prevalence of overweight and eutrophy, which values decreased with age. Leg circumference (LC) (36.27 ± 3.84 cm), Arm circumference (AC) (31.39 ± 4.08 cm) and triceps skinfolds (TS) (20.58±7.54mm) values were suit in most cases (96.7, 85 and 83.3%, respectively). Serum total cholesterol values were 198.53 ± 35.2mg/dL, 55% were considered optimum. About 63.3% and 68.3% of the elderlies, respectively, presented a high density lipoproteins (HDL) (53.58± 10.9mg/dL) and triglycerides (TG) (143.97 ± 92.37mg/dL) according to the recommendation and 51.7% of the elderlies had normal glycemia, 38.3% had risk and 10% showed high blood glucose, indicating diabetes. Conclusion: Many elderlies had body mass index (BMI) above normal, indicating overweight or obesity, but the participants can be considered healthy because of AC, LC and TS values, diet habits, health care and lifestyle.

A população de idosos vem aumentando no Brasil e no mundo, indicando a necessidade de rever os cuidados de saúde do idoso em busca de melhor qualidade de vida. Objetivo: Avaliar o estilo de vida e estado de saúde de idosos participantes da Universidade Aberta a Terceira Idade (UNATI) de Franca, SP. Métodos: Sessenta idosos responderam a questionários com questões socioeconômicas, cuidados de saúde, hábitos alimentares e estilo de vida, e passaram por avaliação antropométrica e exames laboratoriais. Resultados: Houve prevalência de mulheres (85%), indivíduos com idade entre 60 e 69 anos (60%), com nível de instrução até ensino médio (60%), aposentados (65%) e com renda de até 5 salários mínimos (73,4%). A maioria dos idosos fazia acompanhamento médico (65%) e uso contínuo de medicamento (78,3%); 80% relataram estar com a pressão arterial controlada, e 100%, não fumar (100%). Dos entrevistados, 71,7% acreditavam que sua alimentação era saudável, 97% faziam as refeições em casa, 85% escolhiam e preparavam seus alimentos, 65% faziam 5-6 refeições por dia, 63% bebiam menos de 1 L água/dia, 90% tinham bom funcionamento do intestino e 43,3% realizavam atividade física regularmente. Apenas 13,3% faziam reposição hormonal, 18,3% consumiam suplemento alimentar e 21,7% ingeriam bebida alcoólica. Os participantes apresentaram índice de massa corporal (IMC) de 27,49 ± 4,5 kg/m², com prevalência em excesso de peso e eutróficos, cujos valores reduziram com a idade. Os valores de circunferência de panturrilha (CP = 36,27 ± 3,84 cm), circunferência do braço (CB = 31,39 ± 4,08 cm) e dobra cutânea tricipital (DCT = 20,58 ± 7,54 mm) demonstraram adequação na maioria dos casos (96,7%; 85% e 83,3% respectivamente). Os idosos apresentaram colesterol (Col) 198,53 ± 35,2 mg/dL, com 55% na faixa considerada ótima. Apresentaram HDL (53,58 ± 10,9 mg/dL) e triglicérides (143,97 ± 92,37 mg/dL) dentro do recomendado 63,3% e 68,3% dos idosos, respectivamente. Estavam com glicemia normal 51,7%; 38,3% na faixa de risco, e 10% com glicemia alta, indicando diabetes. Conclusão: Grande parte dos idosos apresentou IMC acima do normal, com sobrepeso ou obesidade; porém, os participantes podem ser considerados saudáveis pelos parâmetros de CB, CP e DCT, hábitos alimentares, cuidados de saúde e estilo de vida.
Lifestyle and health of an elderly group from Franca, SP
Keywords: Nutritional status; Aging; BMI; Anthropometry; Hematologic tests; Estado nutricional; Idoso; IMC; Antropometria; Exames de sangue